Point pattern analysis on a region of a sphere - Lawrence, T.; Baddeley, Adrian; Milne, R.; Nair, G. (2016)
We develop statistical methods for analysing a pattern of points on a region of the sphere, including intensity modelling and estimation, summary functions such as the K function, point process models, and model-fitting techniques. The methods are demonstrated by analysing a dataset giving the sky positions of galaxies.